PENGARUH PEMBELAJARAN BERBASIS MASALAH BERBANTUAN MODUL DIGITAL TRIGONOMETRI DALAM MENINGKATKAN KEMAMPUAN LITERASI MATEMATIK DAN MINAT BELAJAR - Oktaviana Nirmala Purba; Mapilindo Mapilindo; Atikah Rahmah Nasution; Rizka Fahruza Siregar (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This research aims to identify the increase in students' mathematical literacy skills and interest in learning after using problem-based learning assisted by digital trigonometry modules, as well as to see the interaction between problem-based learning assisted by digital trigonometry modules and gender on increasing students' mathematical literacy abilities and interest in learning. This research is a quasiexperimental research with a research sample of 69 students with class X-4 as many as 34 students as the experimental class and class X-3 as many as 35 students as the control class. The data obtained from this research are pretest and posttest data on students' mathematical literacy abilities and a questionnaire on students' learning interest. The instruments used to collect this data were tests of students' mathematical literacy skills and interest in learning. The collected data was then analyzed using two-way ANOVA in the SPSS program. Based on the results of data analysis, it was found that the increase in mathematical literacy skills and interest in learning for students who received problem-based learning assisted by digital trigonometry modules was higher than the increase in mathematical literacy skills and interest in learning for students who received regular learning. There is no interaction between the problem-based learning model assisted by digital trigonometry modules and gender on increasing students' mathematical literacy skills and interest in learning. Keyword: Gander, Mathematical Literacy, Interest in Learning, Digital Trigonometry Module, Problem Based Learning. Abstrak: Penelitian ini bertujuan untuk mengidentifikasi peningkatan kemampuan literasi matematik dan minat belajar siswa setelah menggunakan pembelajaran berbasis masalah berbantuan modul digital trigonometri, serta untuk melihat interaksi antara pembelajaran berbasis masalah berbantuan modul digital trigonometri dan gender terhadap peningkatan kemampuan literasi matematik dan minat belajar siswa. Penelitian ini merupakan penelitian eksperimen semu dengan sampel penelitian sebanyak 69 siswa dengan kelas X-4 sebanyak 34 siswa sebagai kelas eksperimen dan kelas X-3 sebanyak 35 siswa sebagai kelas kontrol. Data yang diperoleh dari penelitian ini adalah data pretest dan posttest kemampuan literasi matematik siswa dan angket minat belajar siswa. Instrumen yang digunakan untuk mengumpulkan data tersebut adalah tes kemampuan literasi matematik dan minat belajar siswa. Data yang dikumpulkan tersebut kemudian dianalisis dengan menggunakan anava dua jalur pada program SPSS. Berdasarkan hasil analisis data diperoleh bahwa peningkatan kemampuan literasi matematik dan minat belajar siswa yang mendapat pembelajaran berbasis masalah berbantuan modul digital trigonometri lebih tinggi daripada peningkatan kemampuan literasi matematik dan minat belajar siswa yang mendapat pembelajaran biasa. Tidak terdapat interaksi antara model pembelajaran berbasis masalah berbantuan modul digital trigonometri dan gender terhadap peningkatan kemampuan literasi matematik dan minat belajar siswa. Kata kunci: Gander, Literasi Matematik, Minat Belajar, Modul Digital Trigonometri, Pembelajaran Berbasis Masalah.